Effect of non-alcoholic compounds of alcoholic drinks on the pancreas - Feick, Peter; Gerloff, Andreas; Singer, Manfred V. (Pancreatology, 2007)
Over the past 30 years the role of alcohol (ethanol) in the development of acute and chronic pancreatitis has been intensively investigated. However, ethanol is generally consumed in form of alcoholic beverages which contain numerous non-alcoholic compounds. At least on gastric acid secretion it has been convincingly demonstrated that alcohol and alcoholic beverages have markedly different effects. In the present article, we provide an overview about the effect of different non-alcoholic constituents of alcoholic beverages on the pancreas and their possible interaction with molecular mechanisms leading to ‘alcoholic’ pancreatitis. The present data indicate that pancreatic enzyme secretion in humans is stimulated by non-alcoholic constituents of beer which are generated by alcoholic fermentation of glucose. In addition, it has been shown that natural phenolic compounds (e.g. quercetin, resveratrol) of alcoholic beverages exert different effects on the pancreas in vitro, such as inhibition of pancreatic enzyme output, of pancreatic stellate cell activation and of pancreatic cancer growth as well as protective effects against oxidative stress and on experimental induced acute pancreatitis in rats. However, it should be pointed out that alcoholic beverages contain much more non-alcoholic ingredients. Since the effects of these are still unknown, caution is required in attempting to define alcoholic etiology of pancreatitis without considering the effect of non-alcoholic compounds of alcoholic beverages.
Gesehen am 16.03.2022